2020
DOI: 10.1136/bmjopen-2019-035757
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the number of unnecessary biopsies of US-BI-RADS 4a lesions through a deep learning method for residents-in-training: a cross-sectional study

Abstract: ObjectiveThe aim of the study is to explore the potential value of S-Detect for residents-in-training, a computer-assisted diagnosis system based on deep learning (DL) algorithm.MethodsThe study was designed as a cross-sectional study. Routine breast ultrasound examinations were conducted by an experienced radiologist. The ultrasonic images of the lesions were retrospectively assessed by five residents-in-training according to the Breast Imaging Report and Data System (BI-RADS) lexicon, and a dichotomic classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 30 publications
3
24
0
Order By: Relevance
“…With BI‐RADS 4a as the cutoff value for benign and malignant breast masses, S‐Detect software was more effective for less experienced radiologists and can significantly improve the diagnostic capabilities of less experienced radiologists 20,33 . Zhao et al explored the added value of CAD software for five less experienced radiologists and found that CAD software played an important role in reducing unnecessary biopsy, which was consistent with our study 21 . Therefore, S‐Detect can be considered as an auxiliary tool to improve diagnostic capabilities and reduce unnecessary biopsy of less experienced radiologists.…”
Section: Discussionsupporting
confidence: 89%
“…With BI‐RADS 4a as the cutoff value for benign and malignant breast masses, S‐Detect software was more effective for less experienced radiologists and can significantly improve the diagnostic capabilities of less experienced radiologists 20,33 . Zhao et al explored the added value of CAD software for five less experienced radiologists and found that CAD software played an important role in reducing unnecessary biopsy, which was consistent with our study 21 . Therefore, S‐Detect can be considered as an auxiliary tool to improve diagnostic capabilities and reduce unnecessary biopsy of less experienced radiologists.…”
Section: Discussionsupporting
confidence: 89%
“…[20] Similar studies have shown that young radiologists and radiologists lacking experience in breast ultrasound diagnosis have bene ted signi cantly from the use of a CAD model, especially for category 4a breast nodules, thereby minimizing unnecessary biopsies. [21,22] The radiologists participating in this study each had several years of experience and classi cation consistency among them reached values greater than 0.6 after referencing the CAD model. In addition, the sensitivity, speci city, and accuracy of classi cation improved with the use of CAD, informing adjustments to the initial diagnoses.…”
Section: Discussionmentioning
confidence: 88%
“…Despite these limitations, we believe this study is a meaningful contribution to the emerging field of AI-based decision support systems for interpreting breast US exams. On a clinically realistic population, our AI system achieved a higher diagnostic accuracy (AUROC: 0.976, 95% CI: 0.972, 0.980) than prior AI systems for breast US lesion classification (AUROC: 0.82-0.96) [32,34,48,49,50,51,52], though we acknowledge these systems can be compared only approximately as they were evaluated on different datasets. Key features that contributed to our AI system's high level performance were the large dataset used in training, along with utilization of the weakly supervised learning paradigm that enables the system to learn from automatically extracted labels.…”
Section: Discussionmentioning
confidence: 96%